Rural Futures in Late Socialist Asia: The Countryside in a Globalising World - Mao, Jingyu; Nguyen, Minh T.N.; Wilcox, Phill (Journal of Political Sociology, 2025)
Recent decades have witnessed global movements and flows of labour, capital, goods, and technologies into and out of the countryside in the Global South. This special issue discusses how globalisation, increasing urbanisation, and state policies shape rural lives across China, Vietnam and Laos, and how rural people imagine their futures amid the risks and uncertainties generated at the juncture between political, economic, and ecological forces. It unsettles the urban/rural divide while showing that such polarized construction will persist as long as clear benefits for the state and market remain in constructing the countryside as in dire need of development and catching up with the city.